Operation analysis of the air-source heat pump using TRNSYS simulation tool - Gabrielė Daugirdaitė (Vilnius Gediminas Technical University, 2021)
In order to achieve ambitious goals for energy efficiency and requirements for near zero energy buildings, various technological solutions enabling the use of renewable energy are proposed and applied. One such rapidly spreading technology is heat pumps. However, the use of air-to-water heat pumps in countries where the cold season is cold and humid has unfavourable conditions for the operation of this equipment during the heating season. As a result, the performance efficiency of the equipment decreases. This article presents the simulation results of an air-to-water heat pump operation in Lithuania using the TRNSYS modelling tool; its nominal heating capacity is 6.55 kW. The model was calibrated using real data obtained at Vilnius Gediminas Technical University when measurements were performed under heat pump freezing conditions. The seasonal performance factor of the heat pump heating mode was determined during the calculation. Parametric analysis of the model was also performed, when sensitivity of the model to the initial climatic data was observed. Comparable results are obtained for Vilnius, Prague and London.